The Influence of Direct Reading Thinking Activity (DRTA) Strategy and Know-Want to Know-Learned (KWL) Strategy on Reading Comprehension Skills - Wijaya, Prasetya Andika; sutarto, Joko; Zulaeha, Ida (Universitas Negeri Semarang, 2021)
Reading skills become important role to support his success in the academic field as well as in his daily life. Therefore, for effective learning to be needed the right reading strategy. The aims of this study was to analyze the influence of using the KWL strategy and the DRTA strategy on the reading comprehension skills of fourth grade students. The research design used is a quantitative model in the form of Quasy Experimental Design with a comparative approach. The data collection techniques in this study are test and non-test techniques. The non-test technique in this study used the methods of observation, documentation, and questionnaires. The main indicator measured in this study was comprehension reading skills, which were measured using rubric assessments. The data analysis technique used a prerequisite test, as well as N-gain test, and independent sample t test. The analysis used is comparative analysis, which compares the effectiveness of KWL strategy and DRTA strategy. Based on the results of the study, the DRTA strategy had a positive effect on students' reading comprehension skills by 73.8%, while the KWL strategy also has 64.2%. The DRTA strategy has a positive effect on the reading comprehension results of students by 71.9% and while the KWL strategy has 63.4%. Reading comprehension skills by applying the DRTA strategy obtained an average of 85.6 while the KWL strategy obtained an average of 74.7. It can be concluded that the DRTA strategy has more a positive effect on reading comprehension skills than KWL strategy.